Breast cancer in pregnancy: concurrent cesarean section, nipple-sparing mastectomy, and immediate breast reconstruction—case report - Innocenti, Alessandro; Susini, Pietro; Grimaldi, Luca; Susini, Tommaso (Frontiers in Oncology, 2024)
Pregnancy-associated breast cancer (PABC), with an incidence from 1: 3,000 to 1: 10,000 deliveries, is the most frequent cancer during pregnancy. PABC appropriate management must take into consideration both the maternal oncological safety and the fetal health, thus posing a challenge for mother, baby and clinicians. The treatment should adhere as closely as possible to breast cancer (BC) guidelines. Therefore, surgery is a mainstay and when mastectomy is required, breast reconstruction (BR) is a topic of debate.To minimize the risks to the baby, most surgeons postpone BR to delivery. However, a delayed breast reconstruction (DBR) could affect the outcome. In the present case, we report cesarean section concurrent with mastectomy and immediate breast reconstruction (IBR).A 37-year-old patient, at the 36th week of pregnancy with PABC underwent simultaneous cesarean delivery, nipple-sparing mastectomy and IBR. To minimize risks for the newborn, cesarean was firstly performed under spinal anesthesia. Immediately after, breast surgery, including mastectomy and IBR, was performed under general anesthesia. Partial sub muscular IBR with an acellular porcine dermal matrix concluded the surgical procedure. Lactation was inhibited and adjuvant chemotherapy and hormone therapy were administered to the patient.In a single surgical session, cesarean delivery, subcutaneous mastectomy, axillary dissection, and IBR were successfully carried out. No early or late postoperative complications were reported for both the patient and the newborn. Histopathological investigation reported a multifocal and multicentric infiltrating ductal carcinoma. After a 6-years follow up the patient is alive and well.To the best of our knowledge, this is the first reported case of concomitant cesarean delivery, PABC mastectomy, axillary dissection, and IBR. This surgical strategy allowed PABC treatment by BC guideline, minimizing the newborn's disadvantage and permitting, at the same time the best final BR outcome.